Sistem Informasi Penjualan Gazebo dan Rumah Kayu Berbasis Web Menggunakan Metode CRM (Customer Relationship Management) - Muhammad Zaki; Evi Yulianingsih (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
Sales information system is an information using electronic media. By using this system, it is hoped that customers can find out the latest product information issued by the company and as the best promotional tool so that service to customers will increase. This system is also equipped with product ordering which intends to make it easier for customers to place orders for products. With the creation of this system, companies can find out customer needs and customer desires so that good relationships with customers are established. For this reason, a CRM (Customer Relationship Management) system is needed so that in making a web-based sales information system it can assist customers in obtaining information and provide comfort and convenience for customers. The purpose of this study is to provide product information and order transactions to customers quickly, practically and find out what customers need using the CRM (Customer Relationship Management) method in order to increase sales of gazebos and wooden houses at stores in the city of Palembang. While in making this web-based system with the programming language PHP and MYSQL as the database.